Literature Review On Management Of Atrial Fibrillation And Its Implementation In Rural Areas - Anugerah Pasca; Petrick Aqrasvawinata (Jurnal EduHealth, 2023)
Atrial fibrillation (AF) is a common and chronic heart condition affecting patients in various healthcare settings, including rural clinics. The purpose of this review is to discuss management of AF and its implementation in rural areas. The review employs traditional literature review methodologies through literature obtained from Google Scholar and PubMed. This literature review considers both retrospective and prospective studies, and includes guidelines from official health organizations. Based on the review, AF management often intersects with other health conditions, thus it can be a marker of stroke risk and an indicator of serious diseases. Rural areas physicians face challenges in implementing accurate diagnostics and adopting new treatments while coordinating with specialists to provide comprehensive care. Well-integrated AF management ultimately aims to simplify the treatment options and improve the quality of patient care, especially in rural areas.